Investigating distribution patterns of airborne magnetic grains trapped in tree barks in Milan, Italy: insights for pollution mitigation strategies. Issue 2 (25th May 2017) - Vezzola, Laura C.; Muttoni, Giovanni; Merlini, Marco; Rotiroti, Nicola; Pagliardini, Luca; Hirt, Ann M.; Pelfini, Manuela
Abstract: High levels of air particulate matter (PM) have been positively correlated with respiratory diseases. In this study, we performed a biomonitoring investigation using samples of bark obtained from trees in a selected study area in the city of Milan (northern Italy). Here, we analyse the magnetic and mineralogical properties of the outer and inner barks of 147 trees, finding that magnetite is the prevalent magnetic mineral. The relative concentration of magnetite is estimated in the samples using saturation isothermal remanent magnetization (SIRM) and hysteresis parameters. We also make a first-order estimate of absolute magnetite concentration from the SIRM. The spatial distribution of the measured magnetic parameters is evaluated as a function of the distance to the main sources of magnetic PM in the study area, for example, roads and tram stops. These results are compared with data from a substantially pollution-free control site in the Central Italian Alps. Magnetic susceptibility, SIRM and magnetite concentration are found to be the highest in the outer tree barks for samples that are closest to roads and especially tram stops. In contrast, the inner bark samples are weakly magnetic and are not correlated to the distance from magnetite PM sources. The results illustrate that trees play an important role acting as a sink for airborne PM in urban areas.